2007
DOI: 10.1097/01.pap.0000249906.08602.a6
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Among Patients With Hip Fractures Surgically Repaired Within and After 48 Hours

Abstract: Surgical repair of hip fractures within the first 48 hours was associated with better health outcomes in a nationally representative sample, as observed in an acute care facility, irrespective of comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 14 publications
2
41
0
5
Order By: Relevance
“…The relationship between the timing of surgery and the subsequent mortality risk has been the subject of some debate. There is evidence to suggest that patients who undergo hip fracture stabilization surgery within 48 h of the fracture event are at a reduced risk of death compared with those whose surgery is delayed [68][69][70]. However, there may be a number of barriers to achieving such early surgery including the patient's health status.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the timing of surgery and the subsequent mortality risk has been the subject of some debate. There is evidence to suggest that patients who undergo hip fracture stabilization surgery within 48 h of the fracture event are at a reduced risk of death compared with those whose surgery is delayed [68][69][70]. However, there may be a number of barriers to achieving such early surgery including the patient's health status.…”
Section: Discussionmentioning
confidence: 99%
“…68 Other studies have not shown a decrease in mortality with surgery within 48 hours of admission, 69 but they have revealed decreased minor and major complication rates. 70,71 We believe that once the patient is medically optimized, he or she should be taken to surgery in an expeditious manner to prevent potential complication and possibly improve mortality. However, the literature remains mixed in support of this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Lower mortality rates, fewer complications and decreased length of stay can thereby be obtained. 7,13,[17][18][19][20] …”
Section: Introductionmentioning
confidence: 99%